Genetic variation in Beetal goat breed assest by microsatellite DNA profiling - SHARMA, REKHA; PANDEY, A K; KUMAR, DINESH; ALAM, S; AHLAWAT, S P S (The Indian Journal of Animal Sciences, 2011)
Beetal, one of the important goat breeds of northern India, was investigated genetically utilizing microsatellite markers selected on the guidelines of ISAG and FAO's DADIS (Domestic Animal Diversity Information System) MoDAD programme. The allele and genotype frequencies, heterozygosities and gene diversity were estimated. The observed heterozygosity in the population varied from 0.134-0.842 with the mean of 0.469Â±O.191, indicating lower genetic variation in this population. Bottleneck was examined assuming all three mutation models and was found to be absent. Population displayed heterozygote deficit to the tune of 22.3%. This is the high time to formulate breeding programmes as well as effective conservation strategies for the precious goat breed.Â